The Role of Interfaith Da'wah Communication on Social Media (Study on Dr. Zakir Naik's Youtube Channel Eps. "Why Did Not God Create Only One Religion?") - Khumaeroh, Kholidatul; Susilawati, Nessy (Gema Wiralodra, 2025)
This scientific paper analyzes the episode "Why God Didn't Create One Religion" from the YouTube channel Dr. Zakir Naik as a case study of interfaith communication on the YouTube digital platform. This research aims to understand how Islamic views on religious diversity are presented and their impact on the perceptions of interfaith audiences. This episode explains the concept that religious diversity is part of Divine will which gives humans the freedom to choose their spiritual path. The problem raised in this research is how an interfaith dialogue approach can strengthen tolerance, but also faces challenges, especially regarding perceptions of religious superiority. This research uses a descriptive qualitative analysis method, with data collected from episode observations and audience responses through comments on the YouTube digital platform. The research results show that this episode makes a positive contribution to Muslim audiences' understanding of religious pluralism, especially in terms of acceptance of religious diversity as God's will. However, this episode also gave rise to different perceptions in non-Muslim audiences, where some felt that the presentation positioned Islam as a superior religion, thus potentially causing defensive reactions. Therefore, to increase the effectiveness of interfaith communication, this research recommends using more inclusive language, including the perspectives of figures from other religions, and emphasizing universal values ​​such as justice, compassion and peace. The conclusion of this research is that with a more dialogical approach and respect for diversity, similar episodes can be an effective medium for strengthening tolerance and creating more harmonious interfaith understanding.